Importance of epidermal clocks for regulation of hypocotyl elongation through PIF4 and IAA29. (1st February 2016) - Shimizu, Hanako; Torii, Kotaro; Araki, Takashi; Endo, Motomu
Abstract: Circadian clocks adjust an organism's environmentally relevant physiological responses.. In plants, a decentralized circadian clock system has recently been proposed. Epidermal clock function is crucial for cell elongation; thus, epidermis-specific overexpression of CCA1 caused smaller cotyledons and longer hypocotyls under 27°C, concomitant with elevated night time levels of PIF4 mRNA. However, which tissue's clock regulates PIF4 expression is still an open question. Here we tested spatial expression patterns of PIF4 and its downstream target IAA29 with or without epidermal clock perturbation. Using an epidermal-specific expression system, we revealed that epidermal clock perturbation increases PIF4 expression in both epidermis and mesophyll. However, IAA29 expression is mainly regulated in the epidermis, implying the potential importance of epidermis for regulation of cell elongation through PIF4 and IAA29. We conclude that the circadian clock in epidermis regulates cell elongation mainly in epidermis, and there is also another inter-tissue signaling pathway from epidermis to mesophyll.